Cu/M:ZnO (M = Mg, Al, Cu) colloidal nanocatalysts for the solution hydrogenation of carbon dioxide to methanol. Issue 22 (27th May 2020) - Leung, Alice H. M.; García-Trenco, Andrés; Phanopoulos, Andreas; Regoutz, Anna; Schuster, Manfred E.; Pike, Sebastian D.; Shaffer, Milo S. P.; Williams, Charlotte K.
Abstract : Doped-ZnO nanoparticles, capped with dioctylphosphinate ligands, are synthesised by the controlled hydrolysis of a mixture of organometallic precursors. Abstract : Doped-ZnO nanoparticles, capped with dioctylphosphinate ligands, are synthesised by the controlled hydrolysis of a mixture of organometallic precursors. Substitutional doping of the wurtzite ZnO nanoparticles with 5 mol% Mg(ii ), Al(iii ) and Cu(i ) is achieved by the addition of sub-stoichiometric amounts of the appropriate dopant [( n -butyl)( sec -butyl)magnesium, triethylaluminium or mesitylcopper] to diethylzinc in the precursor mixture. After hydrolysis, the resulting colloidal nanoparticles (sizes of 2–3 nm) are characterised by powder X-ray crystallography, transmission electron microscopy, inductively-coupled plasma optical emission spectrometry and X-ray photoelectron spectroscopy. A solution of the doped-ZnO nanoparticles and colloidal Cu(0) nanoparticles [M:ZnO : Cu = 1 : 1] are applied as catalysts for the hydrogenation of CO2 to methanol in a liquid-phase continuous flow stirred tank reactor [210 °C, 50 bar, CO2 : H2 = 1 : 3, 150 mL min −1, mesitylene, 20 h]. All the catalyst systems display higher rates of methanol production and better stability than a benchmark heterogeneous catalyst, Cu–ZnO–Al2 O3 [480 μmol mmolmetal −1 h −1 ], with approximately twice the activity for the Al(iii )-doped nanocatalyst. Despite outperforming the benchmark catalyst, Mg(ii ) doping is detrimental towards methanol production in comparison to undoped ZnO. X-Ray photoelectron spectroscopy and transmission electron microscopy analysis of the most active post-catalysis samples implicate the migration of Al(iii ) to the catalyst surface, and this surface enrichment is proposed to facilitate stabilisation of the catalytic ZnO/Cu interfaces.